Folk Song Arrangements in Music Ensembles to Promote National Culture at Santo Yosef School Surabaya - Kristiandri, Dhani; Dewi, Vivi Ervina; Sarjoko, Moh.; Suwahyono, Agus; Winarko, Joko (Gondang: Jurnal Seni dan Budaya, 2024)
In this study, the treatment provided is in the form of learning innovation by providing solutions that can invite students to love national culture again through folk song arrangements played in a music ensemble format. The research method used is mix method. The quantitative method uses experimental research type with one-group pretest-posttest design.The first activity carried out was the introduction of a folk song originating from East Java, namely the song "rek ayo rek". After students recognize the form of the song, students are trained to make an arrangement of the song "rek ayo rek". In the next stage, students begin to play the song arrangements that have been made accompanied by the teacher and members of the research team according to their expertise. In the last activity, students present the arrangements that have been made and played in the school performance hall. Before testing the hypothesis, the prerequisite test of analysis used is the normality test with the Kolmogorov Smirnov method. The normality test results obtained a sig value of 0.200 (pretest) and 0.115 (posttest). These results show that the sig value> 0.05, so the data is normally distributed (symmetrical) at pretest and posttest. The average results of the appreciation questionnaire and love of Santo Yosef Junior High School students for national culture in the pretest amounted to 76.15 and posttest amounted to 80.40 from the application of folk song arrangement treatment through music ensemble activities made. Based on these results, the average on the pretest and posttest increased by 4.25. The pretest and posttest conditions of the application of the folk song arrangement treatment through music ensemble activities were correlated at 0.865. This means that the relationship between the two conditions is unidirectional (the value obtained is positive), very strong, and significant because the probability/significance/sig value is smaller than 0.05 (0.000 < 0.05). Thus, learning music ensemble through folk song arrangement approach in Santo Yosef Surabaya Junior High School is said to be effective.